Current management of fistulizing perianal Crohn’s disease based on serum anti-tumor necrosis factor levels and magnetic resonance imaging monitoring - Wolker,Felipe Bernardi (2020)
ABSTRACT Perianal fistulizing Crohn’s disease (PFCD) is one of the most complex challenges in the colorectal surgery nowadays, because, even with combined clinical and surgical treatment, the rate of healing of the fistulas is approximately 50%. In this context, the monitoring of serum levels of anti-Tumor Necrosis Factor (anti-TNF) drugs appears as a crucial tool for the optimization of treatment, since there is a probable correlation between higher serum levels of infliximab and adalimumab with better outcomes of the disease, higher healing rates and lower recurrence rates. This review describes evidence on the use of serum anti-TNF levels and their relationship to clinical and radiological efficacy.